The prophetic imagination - Brueggemann, Walter (Fortress Press, 2018)
"A classic text in biblical theology--still relevant for today and tomorrow. In this 40th anniversary edition of the classic text from one of the most influential biblical scholars of our time, Walter Brueggemann, offers a theological and ethical reading of the Hebrew Bible. He finds there a vision for the community of God whose words and practices of lament, protest and complain give rise to an alternative social order that opposes the "totalism" of the day. Brueggemann traces the lines from the radical vision of Moses to the solidification of royal power in Solomon to the prophetic critique of that power with a new vision of freedom in the prophets. Linking Exodus to Kings to Jeremiah to Jesus, he argues that the prophetic vision not only embraces the pain of the people, but creates an energy and amazement based on the new thing that God is doing. This edition builds off the revised and updated 2001 edition and includes a new afterword by Brueggemann and a new foreword by Davis Hankins"--